THE EFFECT OF FLUID FLOW RATE ON THE CORROSION RATE OF THE PIPE OF SEA WATER SYSTEM - Sambodho, Kriyo; Kusherminto Priyo Pratomo, Kurnia (Department of Marine Engineering, Universitas Hang Tuah, 2024)
Corrosion is a process of decreasing the quality of material because it reacts with the environment. The corrosion process takes place spontaneously and is a natural event that cannot be avoided. This research was carried out to determine the relationship between the fluid flow rate of seawater flowing in the channels of API 5L grade B standard galvanized pipe and seamless pipe specimens on the corrosion rate using flow modelling for 4 months. The research variations used were variations in flow rate, namely 50%, 75%, and 100%. Corroded pipe specimens were cleaned, weighed, and photomicrography. From this research, it was found that the higher the flow rate, the higher the corrosion rate that occurs and the corrosion that occurs is abrasion corrosion and pitting corrosion.